A diet collecting bag for esophageal-fistulated water buffaloes - Camarão, Ari Pinheiro; Batista, Heriberto Antonio Marques (Pesquisa Agropecuaria Brasileira, 2014)
A diet collecting bag for esophageal-fistulated grazing water buffaloes utilized in forage evaluation trials at the Centro de Pesquisa Agropecuária do Trópico Úmido (CPATU) at Belém, PA, Brazil, is described and illustrated.